Pengaruh Shalat Dhuha Terhadap Pembentukan Karakter Religius Siswa Di Madrasah Aliyah Nurul Islam Pasirwangi Garut - Raito, Raito; LATIFAH, MELA (MASAGI : Jurnal Pendidikan Agama Islam, 2022)
Globalization today has made it challenging for children to perform religious practices, respect others, and resist external cultural influences, leading to issues with students' character development. Character education is crucial as it serves as a nation's foundational pillar and should be instilled in children from an early age. Therefore, instilling religious character through the practice of Dhuha prayer is one of the strategies implemented. Teachers have designed religious character formation programs to enhance students' personalities and their religiousness through Dhuha prayer activities. This study aims to assess the implementation of Dhuha prayer at MA Nurul Islam Pasirwangi Garut and evaluate the religious character among students at the institution. It seeks to determine the extent to which Dhuha prayer practice influences the development of students' religious character in their daily lives. The study employs an inferential quantitative method to examine the relationship between Variable X (Dhuha prayer implementation) and Variable Y (religious character formation), involving 25 participants. Data were collected using questionnaires, which served as research instruments, providing comprehensive, systematic, and easily analyzable data. The results indicate that the average implementation of Dhuha prayer among students is 4.056, falling within the 3.01-4.00 interval, categorized as good. The religious character formation has an average score of 3.976, also within the 3.01-4.00 interval, and is categorized as good. Statistical analysis reveals that Dhuha prayer practice influences the development of students' religious character by 38.59%, which is considered high. However, 61.41% of other factors influencing the formation of religious character were not explored in this study. Keywords: Dhuha Prayer Implementation, Religious Character Formation, Students' Religious Character